THE INTERPRETATION OF THE SHAIKHS IN «DURRUL MAJOLIS» BY SAIF ZAFARI BUKHARY (TAMADDUN NURI JURNALI, 2024)
In the article, the stories related to the sheikhs presented in the work «Durrul Majolis» stored in the Bukhara Regional Library named after Abu Ali Ibn Sina under inventory number 726, are subjected to an ideological and artistic analysis. This work was published in 1910 at the Gholomi printing house in Tashkent. However, unlike the works of the same nature, this book also contains stories related to some Companions and saints. The article analyzes stories related to Sultan Bayazid Bistomi, Sultan Ibrahim Adham.